2006
DOI: 10.1097/01.sap.0000235455.21775.6a
|View full text |Cite
|
Sign up to set email alerts
|

New Aspects of Breast Volume Measurement Using 3-Dimensional Surface Imaging

Abstract: Precise and objective calculation of breast volume is helpful to evaluate the aesthetic result of breast surgery, but traditional methods are unsatisfactory. Three-dimensional (3D) scanning of the body surface allows reproducible and objective assessment of the complex breast region but requires further investigation before clinical application. The main goal of this study was to investigate the precision and accuracy of breast volume measurement using 3D body scanning. Five independent observers standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 18 publications
7
94
1
Order By: Relevance
“…Edsander-Nord in their study concluded that using thermoplastic cast seems to be sufficiently accurate to measure breast volume [6] . Kovacs et al in 2007 calculated breast volume using MRI showed the best agreement with 3D scanning measurement (r=0.990), followed by anthropomorphic measurement (r=0.947) and thermoplastic castings (r=0.727) [7] . Grossman and…”
Section: Discussionmentioning
confidence: 99%
“…Edsander-Nord in their study concluded that using thermoplastic cast seems to be sufficiently accurate to measure breast volume [6] . Kovacs et al in 2007 calculated breast volume using MRI showed the best agreement with 3D scanning measurement (r=0.990), followed by anthropomorphic measurement (r=0.947) and thermoplastic castings (r=0.727) [7] . Grossman and…”
Section: Discussionmentioning
confidence: 99%
“…By applying a standardized 3-D scanning protocol, the influence of human artefacts can be compensated and reduced [13][14][15][23][24][25][26]. 3-D imaging of the breast region for example can be obtained in a standing position on predefined markers on the ground, patients back-supported by a wall, patients holding their breath during acquisition and arms down the side crossed behind at the height of the pelvis [3,15,23,25]. In addition, Patete et al presented a methodology for active compensation of breathing motion and involuntary movements to obtain a reliable and artefact-free patient's body surface during the 3-D acquisition [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, different three-dimensional (3-D) optical scanning systems have been applied in medicine to improve preoperative planning and surgical outcome research, most widely used in plastic and reconstructive surgery [1][2][3][4] and cranio-maxillo-facial surgery [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This analysis could be either a twodimensional e.g. using photographs or three-dimensional analysis [18,19] and lead to better understanding of role of preoperative and postoperative cleavage morphology in patient satisfaction.…”
Section: "Craniocaudal" or "Bird's Eye" Viewmentioning
confidence: 99%